Pengaruh Budaya Organisasi Dan Komunikasi Interpersonal Dengan Komitmen Karyawan Es.Clo - Maudy Rizkiana Poedjadi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
In a company, organizational culture and interpersonal communication between employees often have great significance in work commitments because commitments are related to acceptance, health, and maintenance. With this phenomenon, research wants to know how significant the relationship with commitment is through organizational culture and the effectiveness of interpersonal communication. This research was conducted on employees of Es. Clo is a clothing start-up in Bandung, Indonesia. The population in this study was 15 people; considering the small population, the researchers took all employees as samples. Through quantitative research methods and the positivism paradigm, researchers tested multiple regression analysis to see the influence of organizational culture and interpersonal communication's effectiveness on employee work commitment. Based on the study's results, it was shown that there was a positive and simultaneous influence of the two variables on influencing work commitment. This was shown from the ANOVA table test, which showed a positive influence between organizational culture and interpersonal communication with Es. Clo's employee commitment. The organizational culture of the Es. Employees have understood Clo company in terms of rules, norms, dominant values ​​, and organizational climate.